First, expand the term on the left using this special rule for multiplying quadratics:
(color(red)(x) + color(blue)(y))^2 = color(red)(x)^2 + 2color(red)(x)color(blue)(y) + color(blue)(y)^2(x+y)2=x2+2xy+y2
Substituting gives:
(color(red)(-2x) + color(blue)(5))^2 = -8(−2x+5)2=−8
(color(red)(-2x))^2 + (2 * color(red)(-2x) * color(blue)(5)) + color(blue)(5)^2 = -8(−2x)2+(2⋅−2x⋅5)+52=−8
4x^2 + (-20x) + 25 = -84x2+(−20x)+25=−8
4x^2 - 20x + 25 = -84x2−20x+25=−8
We can next convert this to standard form:
4x^2 - 20x + 25 + color(red)(8) = -8 + color(red)(8)4x2−20x+25+8=−8+8
4x^2 - 20x + 33 = 04x2−20x+33=0
We can now use the quadratic formula to find the solutions for xx. The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0ax2+bx+c=0, the values of xx which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))x=−b±√b2−(4ac)2⋅a
Substituting:
color(red)(4)4 for color(red)(a)a
color(blue)(-20)−20 for color(blue)(b)b
color(green)(33)33 for color(green)(c)c gives:
x = (-(color(blue)(-20)) +- sqrt(color(blue)(-20)^2 - (4 * color(red)(4) * color(green)(33))))/(2 * color(red)(4))x=−(−20)±√−202−(4⋅4⋅33)2⋅4
x = (color(blue)(20) +- sqrt(400 - 528))/8x=20±√400−5288
x = (color(blue)(20) +- sqrt(-128))/8x=20±√−1288
x = (color(blue)(20) +- sqrt(64 * -2))/8x=20±√64⋅−28
x = (color(blue)(20) +- sqrt(64)sqrt(-2))/8x=20±√64√−28
x = (color(blue)(20) +- 8sqrt(-2))/8x=20±8√−28
Or
x = color(blue)(20)/8 +- (8sqrt(-2))/8x=208±8√−28
x = 5/2 +- sqrt(-2)x=52±√−2